PENGARUH IMPLEMENTASI KURIKULUM MERDEKA BELAJAR TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL KELAS IV DI SEKOLAH DASAR NEGERI 20 MAKRAMPAI TAHUN PELAJARAN 2024-2025 - Ismawati Ismawati; Eliyah Eliyah; Maskupah Maskupah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to obtain complete, detailed, accurate, and in-depth information about the impact of the implementation of the Independent Learning Curriculum on cognitive learning outcomes of students in Science and Social Studies subjects in the 4th grade at SD Negeri 20 Makrampai for the 2024-2025 academic year. The research is quantitative, using a survey research method. The study population consists of 27 4th-grade students at SD Negeri 20 Makrampai. Data were collected through a questionnaire consisting of 21 statements and a multiple-choice test consisting of 20 questions. Data analysis techniques used descriptive statistics and simple linear regression. The research findings indicate that: 1) The implementation of the Independent Learning Curriculum is in very good condition, with a percentage of 83.2%; 2) Cognitive learning outcomes of students in Science and Social Studies subjects in the 4th grade are in good condition, with a percentage of 80.92%; 3) There is no significant influence between the implementation of the Independent Learning Curriculum and cognitive learning outcomes of students in Science and Social Studies subjects in the 4th grade at SD Negeri 20 Makrampai. This is because the sig value obtained is 0.310, which is greater than the significance level of 0.05. However, the relationship between the two variables is positive, meaning that the better the implementation of the Independent Learning Curriculum, the higher the cognitive learning outcomes of students in Science and Social Studies. The R Square value obtained is 4.1%, indicating that the contribution of the Independent Learning Curriculum to cognitive learning outcomes in Science and Social Studies is 4.1%, while the remaining 95.9% is influenced by other factors.